Idem proti ipse - Čale, Morana (Primerjalna književnost, 2007)
The novels Uno, nessuno e centomila (One, No One, and One Hundred Thousand) by Luigi Pirandello and Na rubu pameti (On the Edge of Reason) by Miroslav Krleža highlight the split between the quantitative-qualitative identity (idem-identity) and the reflexive self (ipse-identity). In structurally homologous ways they therefore articulate the interdependence between narration and the constitution of personal identity.
Keywords: Pirandello, Luigi, 1867-1936; Krleža, Miroslav, 1893-1981; naratologija; narratology; pripovedovalec; pripovedna tehnika; hrvaška književnost; italijanska književnost